2020
DOI: 10.1155/2020/3089094
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Sedation on Adenoma Detection Rate and Cecal Intubation Rate in Colonoscopy

Abstract: Purpose. To explore the effect of sedation on the quality of colonoscopy. Methods. The data collected from the Digestive Endoscopy Center of Shanghai Tongji Hospital from March 2012 to June 2019 were retrospectively analyzed. The rate of sedation and quality metrics of colonoscopy such as adenoma detection rate (ADR) and cecal intubation rate (CIR) were calculated. The logistic regression model was used to explore the relationship between sedation and quality metrics of colonoscopy. The interaction effects bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…Zhao 19 et al found no help on ADR or PDR of sedation, but multivariate analysis for evaluating confounding factors were not performed. Huang and Zhang 7,20 et al found that sedation was a favorable factor to improve ADRs, but the history of colorectal disease didn't been investigated. Khan 21 et al also found that sedation as opposed to no sedation was signi cantly associated with a higher ADR, but only 179 of 24,795 patients underwent unsedated colonoscopies, which was too small to draw robust conclusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhao 19 et al found no help on ADR or PDR of sedation, but multivariate analysis for evaluating confounding factors were not performed. Huang and Zhang 7,20 et al found that sedation was a favorable factor to improve ADRs, but the history of colorectal disease didn't been investigated. Khan 21 et al also found that sedation as opposed to no sedation was signi cantly associated with a higher ADR, but only 179 of 24,795 patients underwent unsedated colonoscopies, which was too small to draw robust conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Sedation has become a common practice in endoscopic operation over the past decades [5][6][7] . Several previous studies have shown that sedation could reduce pain of patients and improve the operator satisfaction, thus shortened the time of colonoscopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatima Khan revealed that colonoscopy with sedation, as opposed to no sedation, was significantly linked to higher ADR ( 37 ). Qiongmei Zhang indicated that sedation was an independent factor associated with higher ADR ( 38 ). A study revealed that midazolam/fentanyl sedation administered by colonoscopists might increase PDR during colonoscopy ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are conflicting data regarding the influence of sedation on ADR. In some studies ADR was significantly higher when colonoscopies were performed with sedation (Khan et al, 2020;Zhang et al, 2020), and in others ADR was not influenced by sedation (Bannert et al, 2012;Lee et al, 2014;Zhao et al, 2020) but the frequency of major complications increased among sedated patients (Zhao et al, 2020). We have not found studies in which Frontiers in Pharmacology frontiersin.org sedation negatively influences ADR, and the data we obtained may represent a particularity that deserves to be studied further or may be a false positive finding determined by the limitations of the study.…”
Section: Discussionmentioning
confidence: 99%